Composition and spatio-temporal dynamics of aquatic bird community in humid areas of Alto Parana Atlantic Forest - Lima, B. M.; Ragusa-netto, J.; Donatelli, R. J. [UNESP]; Posso, S. R. (Instituto Internacional de Ecologia, 2021)
The northwestern portion of the Upper Paraná Atlantic Forest ecoregion is one of the most disturbed and fragmented areas in the Atlantic Forest, and little is known about the local avifauna. In this study, we have described the composition and diversity of the aquatic avifauna of this region and analyzed the patterns of similarity with respect to the seasonal as well as spatial distribution. We used the line transect sampling technique in six distinct humid areas (including lentic and lotic water bodies) during the dry and rainy seasons of 2012 and 2013. A total of 52 species of waterfowl were recorded. The species richness of the studied areas was surprisingly distinct; only seven waterfowl species, namely Cairina moschata (Linnaeus, 1758), Tigrisoma lineatum (Boddaert, 1783), Rosthramus sociabilis (Vieillot, 1817), Aramus guarauna (Linnaeus, 1766), Vanellus chilensis (Molina, 1782), Jacana jacana (Linnaeus, 1766), and Arundinicola leucocephala (Linnaeus, 1764), were common to these six studied areas. This indicated that the other bird species that were observed might be habitat selective. Moreover, the analysis of the composition of birds in the two seasons (dry and rainy) combined with their spatial distributions showed significant dissimilarities between the areas with lotic (river and constructed wetland) and lentic (lagoons) characteristics. Nevertheless, despite the small extent and low total richness of the entire study area, it was found to be home to 1/3 of all freshwater aquatic birds documented in the state of São Paulo, with the record of 5 migratory species and 11 new species added to the northwest of the state. The heterogeneity of local aquatic environments, habitat selection combined with seasonality, and the absence of other humid locations in the surroundings can explain the diversity and distribution of these birds in the water bodies of this uninvestigated Atlantic Forest ecoregion.

A porção noroeste da ecorregião Floresta Atlântica do Alto Paraná é uma das mais alteradas e fragmentadas da Mata Atlântica, da qual pouco se sabe sobre a avifauna local. Nosso objetivo foi descrever a diversidade e composição da avifauna aquática, bem como analisar os padrões de similaridade quanto a distribuição temporal e espacial destas aves nesta ecorregião. Utilizamos a transecção linear para amostragem em seis áreas úmidas (corpos d’água lênticos e lóticos), nos períodos de seca e chuva entre 2012 e 2013. Registramos 52 espécies de aves aquáticas e as riquezas das áreas mostraram-se distintas, pois apenas Cairina moschata (Linnaeus, 1758), Tigrisoma lineatum (Boddaert, 1783), Rosthramus sociabilis (Vieillot, 1817), Aramus guarauna (Linnaeus, 1766), Vanellus chilensis (Molina, 1782), Jacana jacana (Linnaeus, 1766), and Arundinicola leucocephala (Linnaeus, 1764) foram comuns às seis áreas, o que indica seleção de habitat. Quando analisada a composição das aves nos dois períodos aliada à distribuição espacial, encontramos dissimilaridades temporais acentuadas entre os ambientes com características lóticas (rio e aterro) e lênticas (lagoas). Isto mostra que, além das diferentes épocas sazonais, é necessário analisar separadamente os diferentes tipos de áreas úmidas. Por fim, apesar da extensão pequena e baixa riqueza total, a área amostrada abrigou 1/3 das aves aquáticas de água doce para o estado de São Paulo, cinco espécies migratórias e 11 novas espécies para o noroeste do estado. A heterogeneidade de ambientes aquáticos locais, forte seleção de habitat aliada à sazonalidade e ausência de outros locais úmidos em seu entorno, explicam a diversidade e distribuição destas aves estreitamente relacionadas aos corpos d’água desta desconhecida ecorregião da Mata Atlântica.
Composição e dinâmica espaço-temporal da comunidade de aves aquáticas em áreas úmidas da Floresta Atlântica do Alto Paraná
Keywords: wet areas; bird assembly; waterfowl; environment heterogeneity; áreas úmidas; assembleia de aves; ecologia; heterogeneidade de ambientes